POLITICAL DEVELOPMENT OF KAZAKHSTAN: RESULTS AND PROSPECTS - ZHILTSOV, Sergey; ZONN, Igor (CENTRAL ASIA AND THE CAUCASUS, 2019)
Kazakhstan has been following its own path of social development that differed significantly from its Central Asian neighbors: it did not opt for total democratization as Kyrgyzstan did (which was viewed at a certain time as the region’s most democratic country) and was not tempted by the autocratic trends typical of Turkmenistan and Uzbekistan, where, back in 1992, the president became the central figure with the parliament and the judicial system pushed aside. Kazakhstan took time to build up its political system, where the president invariably remained the main figure. The First President of Kazakhstan, Nursultan Nazarbayev, played a crucial role in the political processes unfolding in the country and its development as a whole. His well-balanced foreign policy helped avoid the shocks of economic reforms and political upheavals inside and outside the country, establishing good relationships with its Central Asian neighbors as well as with Russia, the U.S., and China.For a long time, the First President consistently consolidated the executive power vertical to concentrate it in the hands of the president and stabilize the social and economic situation by keeping the multifaceted influence of regional elites in check. However, the consolidation of presidential power caused certain political problems that negatively affected the country’s development, namely, a lack of political elite rotation and the complete domination of the president in a country where the parliament had no independent role to play. The political system, therefore, was adjusted to the interests of Nazarbayev and his closest circle, which became especially clear when he decided that the time had come to start looking for ways and means to preserve political stability and remain in control. It was vitally important to continue his well-balanced foreign policy, prevent cardinal changes in the balance of power inside the country, and ensure the continuity of power. However, changes at the country’s highest post could no longer be postponed, which explains why, in recent years, the First President of Kazakhstan has been working hard to resolve the problem.